Le public et le privé dans Mesure pour Mesure - Michèle Vignaux (Sillages Critiques)
Through such questions as the topos of seeming vs. being, the conflicts between secret spousals and marriage, the importance of reputation as a condition of the reliability of witnesses and its vulnerability to rumour and slander, or even through the “mysteries” of trade guilds, the relationships between public and private life lie at the heart of Measure for Measure. The initial black-and-white picture and clear-cut dichotomy of sin and virtue gradually gives way to an increasingly complex and unsettling picture resulting from the intricacies of doubts, uncertainties, fears, casuistry, perversion, and various forms of manipulation. In this article, I will focus on the dialectics of light and darkness, ostentation and secrecy, dissimulation and display, throughout the play and up to the very last line, with its paradoxical promise to show “What’s yet behind that’s meet you all should know” (5.1.536).